Type and Pattern of Alcohol Consumption is Associated With Liver Fibrosis in Patients With Non-alcoholic Fatty Liver Disease. (October 2018) - Mitchell, Tim; Jeffrey, Gary; de Boer, Bastiaan; MacQuillan, Gerry; Garas, George; Ching, Helena; Hamdorf, Jeffrey; Adams, Leon
Abstract Introduction It is unclear whether low levels of alcohol are harmful in patients with non-alcoholic fatty liver disease (NAFLD). We aimed to determine whether quantity, binge pattern consumption, or type of alcohol was associated with liver fibrosis in patients with NAFLD. Methods Previous and current alcohol consumption was assessed in NAFLD patients undergoing liver biopsy. All subjects currently consumed <210 g per week (male) or <140 g per week (female). Binge consumption was defined as ≥4 standard drinks (female) or ≥5 standard drinks (male) in one sitting. Liver biopsies were scored according to the NASH CRN system with F3/4 fibrosis defined as advanced. Results Among 187 patients (24% with advanced fibrosis), the median weekly alcohol consumption was 20 (2.3–60) g over an average of 18 years. Modest consumption (1–70 g per week) was associated with lower mean fibrosis stage compared to lifetime abstainers (p  < 0.05) and a decreased risk of advanced fibrosis (OR 0.33, 95% CI 0.14–0.78, p  = 0.01). The association with reduced fibrosis was not seen in subjects drinking in a binge-type fashion. Exclusive wine drinkers but not exclusive beer drinkers, had lower mean fibrosis stage and lower odds of advanced fibrosis (OR 0.20, 95% CI 0.06–0.69, p  = 0.01), compared to lifetime abstinent subjects. No interaction between gender and alcohol quantity, type, or binge consumption on fibrosis was observed. Discussion Modest (1–70 g per week) alcohol consumption, particularly wine in a non-binge pattern, is associated with lower fibrosis in patients with NAFLD. Prospective longitudinal studies into fibrosis progression, cardiovascular outcomes, and mortality are required before clinical recommendations can be made.